Marginalization of end-user stakeholder's in public private partnership road projects in Nigeria. Issue 11 (18th August 2022) - Toriola-Coker, Luqman Olalekan; Alaka, Hafiz; Agbali, Mohammed; Bello, Wasiu Adeniran; Pathirage, Chaminda; Oyedele, Lukmon
Abstract: The operational phase of public private partnership (PPP) projects in Nigeria has consistently witnessed serious challenges. Researches by various authors suggest that the major factors militating against the successful growth and development of PPP projects in Nigeria and other developing countries of the world is the marginalization of end-user stakeholder in PPP projects. As such, this study set out to reveal factors affecting the successful management of the diverse interests of end-user stakeholders of the PPP road projects in Nigeria. Using factors from related literature, a questionnaire was developed and distributed to users of two major PPP road in operation in Nigeria: Lekki/Epe Toll and Apakun Murtala Mohammed PPP toll road. A total of 282 questionnaires were returned representing 70.5% response rate. Cronbach's alpha test was used to check reliability levels of the questionnaire variables (i.e., Likert scale questions) while factor analysis was used to establish the underlying factors affecting the successful participation of end-users stakeholders in PPP road in Nigeria. These underlying factors were fully discussed. It was concluded that active involvement of end-users stakeholders in decision-making from inception to conclusion will solve the problem of marginalization of end-user stakeholder's in Nigeria PPP road projects.